Clinical efficacy analysis of the Chinese medicine Paiteling applied to human papillomavirus infection: A retrospective study. - Na He; Lin Song; Zhaoxia Lu; Qingsong Zeng; Wumei Jin; Wenrong He; Cunjian Yi (PLoS ONE)
Aim To investigate the clinical efficacy of population-based treatment of human papillomavirus (HPV) infections with Paiteling. Methods Between 1 June 2024 and 31 August 2024, 575 HPV-infected patients attending The First People's Hospital of Jingzhou gynecology outpatient clinic from October 2020 to December 2023 were retrospectively collected, all of whom were analyzed for HPV subtype infection and the presence or absence of cytomorphological abnormality using HPV-DNA testing and TCT; they were divided into 319 cases in the Paiteling group and 256 cases in the Interferon group, and the patients of both groups were subjected to TCT 1 month after the end of the administration of the medication and HPV review. Results 1. The three most frequent subtypes of HPV in this data are HPV 16, HPV 52, and HPV 58, all of which are high-risk types; 2. The results of the post-treatment review of HPV infection showed that the overall effective rate of the Paiteling group was better than that of the Interferon group, and the difference in the cumulative effective rate between the two groups was statistically significant (P < 0.001); 3. Comparative analysis of patients with 14 high-risk types of human papillomavirus in a single infection showed that the overall conversion rate in the Paiteling group was 76.3%, higher than that of the Interferon group, which was 36.7%. The difference was statistically significant (P < 0.001). Conclusion The overall efficacy of Paiteling for cervical HPV infection is significantly better than that of Interferon, and it is worth promoting its use in the clinic.